2010
DOI: 10.1007/s10531-010-9866-1
|View full text |Cite
|
Sign up to set email alerts
|

Encroachment of upland Mediterranean plant species in riparian ecosystems of southern Portugal

Abstract: Riparian ecosystems have unique biodiversity, are highly sensitive to disturbance and anthropogenic influence. As world water resources become scarcer, scientists predict greater competition among species for water resources. Indeed, increased encroachment of upland plants into the riparian zone is already occurring, irreversibly changing riparian plant communities. Since semi-arid regions such as Mediterranean-type ecosystems are likely to follow this same trajectory, assessing the contributions of riparian v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 42 publications
3
25
0
1
Order By: Relevance
“…However, in specific cases, the reduction in channel mobility may increase the overall landscape diversity by facilitating expansion of woodland communities (Liébault & Piégay, 2002;Kondolf et al, 2007;Piégay et al, 2009) and human disturbances can increase the total species diversity and evenness (Kladis et al, 2011). Lastly, human-mediated invasion by nonnative species can result in altered competitive hierarchies both for establishing seedlings and for adult plants Aguiar et al, 2006;Stromberg et al, 2007;Mortenson & Weisberg, 2010;Santos, 2010).…”
Section: Human Impactsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in specific cases, the reduction in channel mobility may increase the overall landscape diversity by facilitating expansion of woodland communities (Liébault & Piégay, 2002;Kondolf et al, 2007;Piégay et al, 2009) and human disturbances can increase the total species diversity and evenness (Kladis et al, 2011). Lastly, human-mediated invasion by nonnative species can result in altered competitive hierarchies both for establishing seedlings and for adult plants Aguiar et al, 2006;Stromberg et al, 2007;Mortenson & Weisberg, 2010;Santos, 2010).…”
Section: Human Impactsmentioning
confidence: 99%
“…This requires that we consider various human priorities (e.g., aesthetic, economic, cultural values) along with biophysical functions to address multiple management objectives (Piégay et al, 2005;Santos, 2010;Cottet et al, 2010). Assessment methods will need to consider the role of novel riparian habitats, for example those dominated by non-native species (e.g., Stromberg et al, 2007).…”
Section: Applications To Management Of Med-region Riparian Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a particular concern about the invasive cane or giant reed A. donax L. (Sanz Elorza et al, 2004), declared by the International Union for Conservation of Nature as one of the most dangerous and harmful invasive alien plants worldwide (Bañares et al, 2004). A similar invasion phenomenon has been observed in numerous studies where encroachment of terrestrial species as has been observed along other semi-arid rivers (Huxman et al, 2005;Santos, 2010).…”
Section: Interpreting the Observed Riparian Dynamicssupporting
confidence: 85%
“…Furthermore, their topographical, sedimentological and hydrological heterogeneity make them one of the richest ecosystems in terms of species diversity (Naiman et al, 1993). This fact is specially relevant in the riparian zones of Mediterranean-climate regions (Santos, 2010), where they support a dense and productive closed-canopy forest ecosystem relative to the surrounding landscape, which is typically a matrix of xeric woodlands, shrub and grassland communities (Stella et al, 2012). In addition to their high natural biodiversity, riparian zones provide numerous ecosystem functions and services related to water quality, microclimate, structural habitat for wildlife and fish, an energy base for the food web, and bank stability, among others (Naiman et al, 2005).…”
Section: Overviewmentioning
confidence: 99%